THE EFFECT OF PHOTOGRAPHY USING DIGITAL TECHNOLOGY IN DEVELOPING THE FOUNDATIONS OF ARTISTIC WORK AMONG FOURTH GRADE PRIMARY STUDENTS - Ammar Abdul Hamid Katran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims to: Identifying the effect of digital photography in developing the foundations of the artistic work of fourth grade students. To investigate the research objective, the researcher formulated the following hypotheses: The first hypothesis: There are no statistically significant differences between the mean of the experimental group studied using digital technology and the control group that is taught according to the traditional method at the level of (0,05) in the post-skill test. The second hypothesis: There are no statistically significant differences between the mean scores of the experimental group which is taught using digital technology at the level of (0,05) in the tribal and remote skills test. The current research community may be students of the fourth grade in the General Directorate of Education Baghdad Karkh / 2 academic year (2017-2018). The sample of the study was from the students of the fourth grade in primary school Muhanad primary.